The Akan diaspora in the Americas - Konadu, Kwasi (Oxford University Press, 2010)
In his study of the Akan diaspora, Konadu demonstrates how this cultural group originating in Central West Africa both participated in and went beyond the familiar diasporic themes of maroonage, resistance, and freedom.